2016
DOI: 10.1097/mbc.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of ADAMTS-13 and von Willebrand factor multimers in cardiac surgery

Abstract: Acquired thrombotic-thrombocytopenic purpura, one of the main representatives of thrombotic microangiopathies (TMAs), is caused by the accumulation of antibodies against ADAMTS-13. Several cases of postoperative TMAs have been observed during the past few years, but the pathogenesis remains unknown. In addition to this, it is unclear whether the use of extracorporeal circulation (ECC) during cardiac surgery has an influence on the occurrence of cardiac surgery-associated TMA. In this study, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…already described a markedly increased biologic activity of von Willebrand factor after CPB in children , but multimer analysis was not performed in their cohort. In accordance with the findings in adults undergoing cardiac surgery under CPB , the neonates and infants also showed an increase in the absolute values of VWF:Ag, VWF:CB, VWF:RCo and FVIII:C after discontinuation of CPB compared with their preoperative values. This increase is probably a result of VWF release from activated platelets and endothelial cells under CPB conditions, but it does not necessarily reflect the multimer function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…already described a markedly increased biologic activity of von Willebrand factor after CPB in children , but multimer analysis was not performed in their cohort. In accordance with the findings in adults undergoing cardiac surgery under CPB , the neonates and infants also showed an increase in the absolute values of VWF:Ag, VWF:CB, VWF:RCo and FVIII:C after discontinuation of CPB compared with their preoperative values. This increase is probably a result of VWF release from activated platelets and endothelial cells under CPB conditions, but it does not necessarily reflect the multimer function.…”
Section: Discussionsupporting
confidence: 88%
“…extracorporeal circulation support (ECLS) and ventricular assist devices) trigger the development of aVWS . By contrast, recent data in adults showed that CPB does not induce aVWS .…”
Section: Introductionmentioning
confidence: 97%
“…14 Recent investigations could not detect any appearance of new inhibitory ADAMTS-13 antibodies after cardiac surgery. 6 In contrast to these findings, Sridharan et al 24 identified 2 of the patients in their institutional review with immunemediated pTTP. In both reviews, cardiovascular and vascular surgery were identified as the most common procedures leading to pTTP.…”
Section: Discussionmentioning
confidence: 99%
“…Multimers of higher molecular weight are thereby more hemostatically active than smaller multimers. [4][5][6] ADAMTS-13 (a disintegrin and metalloprotease with thrombospondin type 1 motifs, member 13) is the metalloproteinase specifically cleaving VWF into smaller subunits in the circulation by hydrolysis. [7][8][9][10] High shear stress as occurring in the microcirculation seems to be needed to make the cleavage site of the VWF subunit accessible to ADAMTS-13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation